Investigation of the Role of Bacteria in the Development of Acanthamoeba Keratitis. Issue 10 (October 2015) - Nakagawa, Hayate; Hattori, Takaaki; Koike, Naohito; Ehara, Tomoko; Fujita, Koji; Takahashi, Hiroki; Kumakura, Shigeto; Kuroda, Masahiko; Matsumoto, Tetsuya; Goto, Hiroshi
Abstract : Purpose: Recently, much interest has been shown in bacteria extracted from Acanthamoeba strains isolated from patients with Acanthamoeba keratitis (AK). We hypothesized that the bacteria in Acanthamoeba strains may be a contributing factor in the development of AK. To prove this hypothesis, we investigated the involvement of bacteria harbored by Acanthamoeba in causing progressive ocular infection in rabbit corneas. Methods: One Acanthamoeba strain (T4 genotype) that harbored bacteria was isolated from a patient with AK. The Acanthamoeba strain pretreated or not pretreated with levofloxacin (LVFX) was inoculated into rabbit corneas. We also tested the effect of LVFX eye drops on keratitis induced by the Acanthamoeba strain. The infected rabbit eyes were evaluated for clinical scores, Acanthamoeba 18S rDNA and bacterial 16S rDNA numbers were analyzed by the real-time polymerase chain reaction, and the presence of Acanthamoeba was analyzed by histological examination. Results: Inoculation of nonpretreated Acanthamoeba resulted in severe keratitis. In contrast, inoculation of LVFX-pretreated Acanthamoeba did not induce keratitis (mean clinical score, 17.3 vs. 2.3; P < 0.05). Rabbit corneas inoculated with nonpretreated Acanthamoeba followed by topical LVFX therapy developed severe keratitis. In corneas inoculated with nonpretreated Acanthamoeba followed by LVFX therapy, the number of Acanthamoeba 18S rDNA copies was significantly higher than in other groups ( P < 0.05), whereas the bacterial 16S rDNA gene was undetectable. Acanthamoeba cysts were detected by Fungiflora Y staining only in corneas inoculated with nonpretreated Acanthamoeba followed by LVFX therapy. Conclusions: These results suggest that the presence of bacteria in Acanthamoeba may be required for the development of AK. Abstract : Supplemental Digital Content is Available in the Text.